Lean Healthcare Practices and Operational Performance: Safety Climate as a Moderator - Azyyati Anuar; Rohaizah Saad; Rushami Zein Yusoff; Daing Maruak Sadek (International Journal of Supply Chain Management, 2019)
The main propose of this study was to examine the relationship between lean healthcare practices (LHP) (operational and sociotechnical aspects) and operational performance among Malaysias private hospitals. Specifically it aimed at investigating both the moderating role of safety climate on the relationship between operational aspects and sociotechnical aspects on operational performance. Quantitative method was applied for this study with the questionnaires were randomly distributed to 118 private hospitals in Malaysia as the sample. The data collected were analyzed by performing the PLS-SEM technique. The results indicate that operational aspects and sociotechnical aspects improved operational performance, showing that these are the important elements that should be seriously considered by practitioners. However, safety climate as a moderator failed to support the relationship between operational aspects and sociotechnical aspects on operational performance. These findings have contributed theoretically, practically and methodologically with imperative implications to academicians, policy-makers and private hospitals specifically.